Ice age - Saldanha, Carlos (20th Century Fox Home Entertainment, 2002)
Twenty thousand years ago, at the dawn of the Ice Age, three completely mismatched creatures have been brought together by a twist of fate. Sid, a fast-talking and comical sloth, Manfred, a moody woolly mammoth, and Diego, a sinister saber-toothed tiger reluctantly team up to help return a human baby to his father. Before their incredible journey ends, this unlikely trio will confront boiling lava pits, escape treacherous ice tunnels and meet a prehistoric squirrel-rat named Scrat who is frantically trying to bury his beloved acon.